The question is:

Find the first 3 non-zero terms in the MacLaurin series for the function: $$y =e^{-x^2}$$ I have been told to simply substitute the $-x^2$ into the standard MacLaurin series for $e^x$ like so: $$e^{(-x^2)} = \sum_{n=0}^\infty \frac {x^n}{n!}= 1 + (-x^2) + \frac {{(-x^2)}^2}2 + \frac {{(-x^2)}^3}{3!}+...$$ Giving: $$e^{-x^2} = \sum_{n=0}^\infty \frac {{(-x^2)}^n}{n!} = 1 - x^2 + \frac {x^4}2 - \frac {x^6}{3!}+...$$ I realise that this is supposed to be the correct answer, but I can't seem to make it work alongside the definition of MacLaurin series given to me in lectures. We were told that the terms of a MacLaurin series were based on the formula: $$\sum_{n=0}^\infty a_nx^n$$ where $$a_n = \frac {f^n(0)}{n!}$$ assuming $0!=1$.

However, when I use this formula for $e^{-x^2}$, I get the following: $$a_0x^0=\frac {f^0(0)}{0!}x^0=\frac {e^{-(0)^2}}{1}\times1=\frac 11=1$$ $$a_1x^1=\frac {f^1(0)}{1!}x=\frac {-2(0)e^{-(0)^2}}{1}x=\frac 01x=0$$ $$a_2x^2=\frac {f^2(0)}{1!}x^2=\frac {4(0)^2e^{-(0)^2}}{1}x^2=\frac 01x^2=0$$ and so on. Giving:$$e^{-x^2}=1+0+0+0+...$$ Can somebody explain this to me?

  • 3
    $\begingroup$ Your second derivative is wrong. Also, you shouldn't have any infinite sums of exponentials themselves in any of these equations. $\endgroup$ – Ian Jan 19 '16 at 18:41
  • $\begingroup$ Yes, sorry that was a typo, I will edit it $\endgroup$ – Patrick Thorpe Jan 19 '16 at 18:41
  • 1
    $\begingroup$ You didn't edit out the erroneous summation signs (in your second and third equations). Also: If $f(x)=e^{-x^2}$, what is $f''(x)$, in your opinion? And what, therefore, is $f''(0)$? $\endgroup$ – TonyK Jan 19 '16 at 18:45

The substitution method is probably best for what you are trying to do.

On the other hand, if you want to compute the derivatives of $e^{-x^2}$, then you will have to use a combination of the chain rule and the product rule.

$$f(x) = e^{-x^2}$$

$$f'(x) = -2x e^{-x^2}$$

$$f''(x) = - 2 e^{x^2}+ (-2x)^2 e^{-x^2} = (4x^2 -2) e^{-x^2}$$

$$f'''(x) = 8x e^{-x^2} - (4x^2 - 2) (2x) e^{-x^2} = (-8x^3 + 12x) e^{-x^2}$$

This yields:

$f(0)=1$, $f'(0) = 0$, $f''(0) = -2$, $f'''(0) = 0$, etc.


The second derivative is $$[(-2x)e^{-x^2}]'=(-2+4x^2)e^{-x^2}, $$ which evaluated at $x=0$ gives $-2$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.